Efektivitas Literasi Media Dalam Meningkatkan Minat Baca Melalui Kelompok Gerakan Langkat Pintar - Andrial Safitra (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2018)
This study attempts to described on efforts to the implantation of the literasi the media to raise reading interest via the movements langkat smart. Was used in the study research methodology descriptive of with a qualitative approach was adopted over the literasi media. This research result indicates that motion langkat smart as any one group which carries on the function literasi the media make programs literasi who also useful for the society. This can be seen from programs which he made before the pt pgn promised to supply much as illegal stalls never so much as read, music class, a class of art, a class of langkat smart, a basis of ranking 1 and so forth. The implementation of literacy a medium that done by the langkat smart through programs  it to change in the community that they do not want to read become avid reader. This can be seen from the participation of the community and the response of the community towards the program-program literasi a medium that carried out by the motion of langkat smart.